Guzarishi kumitahi-yi markazi-yi Hizbi Dimukratik Khalqi Afghanistan dar kunfiransi sartasari-yi Hizbi Dimukratik Khalqi Afghanistan : (Hizbi Dimukratik Khalqi Afghanistan)
A report made by the Central Committee of the People's Democratic Party of Afghanistan at the national conference of the People's Democratic Party of Afghanistan, presented by comrade Babrak Karmal.